Students’ perception of code-switching functions and effects in English as a foreign language classroom - Sherin Putri Indanna; Iis Sujarwati; Ari Andre Rianyansa (University of Muhammadiyah Malang, 2026)
This study aims to find students’ view towards the implementation of code switching in learning English and its obstacles. Mixed method was used explanatory sequential design to conduct this research. the total population is 32 students. While, the sample of this study was thirty-two students of English Education Department, Muhammadiyah University of Bengkulu, Indonesia. It was just because only one class that the lecturer implemented code switching in English class. Thus, the sampling technique was purposive sampling. Questionnaire and interview were addressed as instruments to answer the research questions. The questionnaire was addressed to thirty-two students, while only fifteen students were interviewed. The data were analyzed quantitively and qualitatively. For quantitative analysis, the data were analyzed by using simple calculation to know the percentage and mean score. For qualitative data analysis, coding was used for it. The result showed that students had positive responses towards the implementation of code switching in English class. In short, code switching can be as one of teaching strategies for students in learning English because it helps them for speaking, even though, those still have limitation. The findings also revealed that teachers believed code-switching provided a clear purpose and had a positive impact on instruction and language development in EFL classrooms by creating a sociable environment. It was also demonstrated that code switching to teachers was effective in EFL classrooms and played an important role in English learning and teaching. The implications of the findings for EFL teachers and language learning settings were discussed.